Relative contribution of V-H+ATPase and NA+/ H+ exchanger to bicarbonate reabsorption in proximal convoluted tubules of old rats - Fiori, M. (2006)
With aging, the kidney develops a progressive deterioration of several structures and functions. Proximal tubular acidification is impaired in old rats with a decrease in the activity of brush border Na+/ H+ exchange and a fall of H-ion flux measured with micropuncture experiments. In the present work we evaluate the contribution of 5-N-ethyl-n-isopropyl amiloride- (EIPA) and bafilomycin-sensitive bicarbonate flux (JHCO3-) in proximal convoluted tubules of young and aged rats. We performed micropuncture experiments inhibiting the Na+/H+ exchanger with EIPA (10-4 M) and the V-H+ ATPase with bafilomycin (10-6 M). We used antibodies against the NHE3 isoform of the Na+/H+ exchanger and the subunit E of the V-H+ ATPase for detecting by Western blot the abundance of these proteins in brush border membrane vesicles from proximal convoluted tubules of young and old rats. The abundance of NHE3 and the V-H+ ATPase was similar in 18-month-old and 3-month-old rats. The bicarbonate flux in old rats was 30% lower than in young rats. EIPA reduced JHCO3- by 60% and bafilomycin by 30% in young rats; in contrast, EIPA reduced JHCO3- by ∼40% and bafilomycin by ∼50% in old rats. The JHCO3- inhibited by bafilomycin was the same in young and old rats: 0.62.nmol · cm-2 · s-1 and 0.71.nmol · cm-2 · s-1, respectively. However, the EIPA-sensitive fraction was larger in young than in old rats: 1.26.nmol · cm-2 · s-1 vs. 0.85 nmol · cm-2 · s-1, respectively. These results suggest that the component more affected in bicarbonate reabsorption of proximal convoluted tubules from aged rats is the Na+-H+ exchanger, probably a NHE isoform different from NHE3. © 2006 The Authors Journal compilation © Blackwell Publishing Ltd/Anatomical Society of Great Britain and Ireland 2006.